Model for Determining the Cost of Smoked Fish Products in determining the Selling - Wauran, Anita Ludia Vivian; Tene, Johanes Herbert; Walangitan, Loula L .L; Sondakh, Nikson (ISAS, 2025)
This research was conducted on MSMEs in Matani Village who produce raw fish into smoked fish through a fish smoking process. In determining the selling price, it is only based on market prices that are influenced by weather conditions and market price fluctuations at that time. In theory, to determine the selling price, one must first determine the cost of the product before determining the selling price. The cost of goods sold or production costs are all costs incurred during the production process in producing products, from raw materials to finished materials ready for sale. This research aims to produce a Model for Determining the Cost of Smoked Fish Products in determining the Selling Price of smoked fish products in order to improve the financial performance of MSMEs. The research uses a Qualitative Descriptive research method with research stages that will. The results of this study produce smoked fish production costs with 3 cost elements, namely raw material costs, direct labor costs and factory overhead costs as elements forming production costs, which are the basis for determining the selling price, by producing a Model for Determining the Cost of Smoked Fish. Keywords : Production, Price, Product, Smoked, Fish